2022
DOI: 10.56501/intjpedorehab.v7i2.649
|View full text |Cite
|
Sign up to set email alerts
|

Case Series on Personalized Pediatric Posterior Zirconia Crowns

Abstract: Pediatric dentists must comprehend children's aesthetic perception because kids are increasingly aware of their own and other children's appearance. Many aesthetic restorations are available on the market, including open-faced stainless-steel crowns, pre-veneered stainless-steel crowns, strip crowns, and polycarbonate crowns, but each has its own drawbacks. Prefabricated zirconia crowns are a new trend among pediatric dentists for restoring carious, damaged, and malformed primary molars and anteriors. Customiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
(7 reference statements)
0
1
0
Order By: Relevance
“…Clinical evaluations have shown that zirconia crowns are comparable to preformed stainless steel crowns (SSCs) in primary molars, with better gingival scores and excellent color match [ 18 ]. They have been found to prevent adhesion of Streptococcus mutans onto their surface, reducing plaque accumulation around the crown and inflammation of surrounding gingiva compared to conventional stainless steel crowns [ 19 ]. This makes zirconia crowns a viable option for reducing the overall microbial density and prevalence in the oral cavity, thus reducing the caries risk in the long term [ 20 ].…”
Section: Reviewmentioning
confidence: 99%
“…Clinical evaluations have shown that zirconia crowns are comparable to preformed stainless steel crowns (SSCs) in primary molars, with better gingival scores and excellent color match [ 18 ]. They have been found to prevent adhesion of Streptococcus mutans onto their surface, reducing plaque accumulation around the crown and inflammation of surrounding gingiva compared to conventional stainless steel crowns [ 19 ]. This makes zirconia crowns a viable option for reducing the overall microbial density and prevalence in the oral cavity, thus reducing the caries risk in the long term [ 20 ].…”
Section: Reviewmentioning
confidence: 99%